2023
DOI: 10.2106/jbjs.cc.23.00060
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Static Posterior Shoulder Subluxation by Restoring Normal Scapular Anatomy Using Acromion and Glenoid Osteotomies

Abstract: Case: A 40-year-old man presented with progressive shoulder pain, associated with static posterior subluxation and mild eccentric glenohumeral osteoarthritis. Compared with a mean statistical shape model of a normal shoulder, the patient's acromion was abnormally high and horizontal, and the glenoid abnormally inclined inferiorly and minimally retroverted. Restoration of normal scapular anatomy using 3-dimensional planned acromial and glenoid osteotomies led to recentering of the joint and full shoulder functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Our study results could explain the high failure rates of conventional operative treatment for posterior instability and incipient eccentric OA [4, 7, 16]. They would suggest combined (glenoid and acromion) osteotomies planned on quantitative 3‐D analyses of individual B1 scapulae and planned restoration of the anatomy as near as possible to the normal shoulder [8].…”
Section: Discussionmentioning
confidence: 98%
“…Our study results could explain the high failure rates of conventional operative treatment for posterior instability and incipient eccentric OA [4, 7, 16]. They would suggest combined (glenoid and acromion) osteotomies planned on quantitative 3‐D analyses of individual B1 scapulae and planned restoration of the anatomy as near as possible to the normal shoulder [8].…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, our experimental setup provides insight into possible biomechanical causes of joint degeneration in shoulder muscle pathology. Furthermore, our simulator may be used to investigate the biomechanical implications of novel surgical approaches such as those involving morphological changes, as shown in a recent case study by Gerber et al [ 39 ], who demonstrated that osteotomy involving morphological modifications of the acromion and glenoid to correct abnormal morphological parameters can lead to improved patient outcomes.…”
Section: Discussionmentioning
confidence: 99%